Towards Personalized Medicine: Microdevice-Assisted Evaluation of Cancer Stem Cell Dynamics and Treatment Response - Agüero, Eduardo Imanol (2025)
Cancer stem cells (CSCs) represent a minor yet critical subpopulation within tumors, endowed with self-renewal and differentiation capacities, and are implicated in tumor initiation, progression, metastasis, therapeutic resistance, and recurrence. Reliable in vitro functional assays to characterize CSCs are pivotal for the development of personalized oncology strategies. This study sought to establish and validate a microfluidic device (MD) platform for the enrichment, functional assessment, and therapeutic evaluation of CSC populations derived from experimental models and primary tumor samples. Methods: Murine (LM38LP) and human (BPR6) breast cancer cell lines were cultured within MDs to promote sphere formation. CSC enrichment was confirmed through the expression analysis of pluripotency-associated genes (Oct4, Sox2, Nanog, and CD44) by quantitative PCR (qPCR) and immunofluorescence. Sphere number, size, and gene expression profiles were quantitatively assessed before (control) and after chemotherapeutic exposure. To validate the MD platform against conventional scale, parallel experiments were performed in 12 well plates. To extend translational relevance, three primary canine tumor samples (solid thyroid carcinoma, simple tubular carcinoma, and reactive lymph node) were mechanically disaggregated and processed within MDs for CSC characterization. Results: The MD platform enabled the consistent enrichment of CSC populations, showing significant modulation of sphere growth parameters and stemness marker expression following chemotherapeutic treatment. Beyond its comparability with conventional culture, the MD also supported immunofluorescence staining and allowed real-time monitoring of individual cell growth. Sphere formation efficiency (SFE) and CSC marker expression were similarly demonstrated in primary veterinary tumor cultures, highlighting the device’s cross-species applicability. Conclusions: Microfluidic-based sphere assays represent a robust, reproducible, and scalable platform for the functional interrogation of CSC dynamics and therapeutic responses. This methodology holds great promise for advancing CSC-targeted therapies and supporting personalized oncology in both human and veterinary settings.